Pengaruh Group Investigation Models Terhadap Peningkatan Kompetensi Mahasiswa - Rajip mustafillah Rusdiyanto; Brio Alfatihah Rama Yudha; Indra Adi Budiman (Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
All pertinent parties must provide the best possible support for government policies pertaining to the Merdeka Learning program. Lecturers are one of the individuals who participate directly in the learning process, giving them the chance to influence it. The curriculum demands that students find all the knowledge and information they require on their own. This study aims to determine how group investigation models affect student competence growth. The approach can be used to assist government projects because it is based on a methodical learning process. utilizing a single group pretest-posttest design and a 64-person sample size. Knowledge, comprehension, application, analysis, evaluation, and creativity are some of the tools used.Through descriptive statistical analysis that offers details about the data collected andstudy findings demonstrating a significant impact on student competence.